COMPARATIVE STUDY ON FEED FORMULATION SOFTWARE- A SHORT REVIEW - Patil, Vishal; Gupta, Radha; D, Rajendran; Singh Kuntal, Ravinder (International Journal of Research -GRANTHAALAYAH, 2017)
The paper highlightsthe different feed formulation software’s for least cost formulation of livestock and animals, where the comparison of techniques is donebased on different aspectslike data collection, software used, price, scope and limitations. Feed formulation requires large amount of data about the composition of feeds, environment conditions,and availability of feeds.Development of Software’sfor feed formulations is changing with change in computer. With advancement of technology, the feed formulation can be calculated for ‘n’ number of feed stuff but still Linear Programming is used as base for mathematical modelling, where uses of non-linear programming is very less. Maximum number of feed formulation software’s is developed to select the feeds for formulation within budget of the farmers or dairy industry.